(untitled) (Modern education and development, 2025)
English is today the foundation of global communication and plays an important role in many fields, including Business, Education, Science and culture. Learning English also helps to form the skills necessary for personal and professional development. Educational technologies, on the other hand, provide new approaches and opportunities for teaching English. This article will consider in detail the advantages of educational technologies in teaching English.